F-actin cytoskeletal organization in intervertebral disc health and disease. (20th July 2007) - Li, S.; Duance, V.C.; Blain, E.J.
Abstract : The cytoskeleton, which in most cell types, including the intervertebral disc described here, comprises microfilaments, microtubules and intermediate filaments, plays important functions in many fundamental cellular events, including cell division, motility, protein trafficking and secretion. The cytoskeleton is also critical for communication; for example, alterations to the architecture of the F-actin (filamentous actin) cytoskeletal networks can affect communication between the cells and the extracellular matrix, potentially compromising tissue homoeostasis. Although there are limited studies to date, this paper aims to review current knowledge on F-actin cytoskeletal element organization in intervertebral disc cells, how F-actin differs with pathology and its implications for mechanotransduction.